2021
DOI: 10.1055/s-0041-1729866
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence in Robotic Colon and Rectal Surgery

Abstract: The indocyanine green fluorescence imaging system is a surgical tool with increasing applications in colon and rectal surgery that has received growing acceptance in various surgical disciplines as a potentially valid method to enhance surgical field visualization, improve lymph node retrieval, and decrease anastomotic leak. Small noncomparative prospective trials have shown that intraoperative fluorescence imaging is a safe and feasible method to assess anastomotic perfusion and that its use may impact anasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
3
0
2
Order By: Relevance
“…22 Additionally, the Firefly system may be utilized in robotic low anterior resection of rectal neoplasms by injecting ICG dye preoperatively to identify these lesions during surgery. 23 This is referred to as "tattooing" and allows the surgeon to confirm they are resecting the oncologic lesion, and to allow optimal healthy tissue conservation. Fluorescent-guided lymph node mapping and subsequent lymphadenectomy have not only been done during distal rectal cancer procedures but also during robotic right hemicolectomy with complete mesocolic excision (CME) for rightsided colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Additionally, the Firefly system may be utilized in robotic low anterior resection of rectal neoplasms by injecting ICG dye preoperatively to identify these lesions during surgery. 23 This is referred to as "tattooing" and allows the surgeon to confirm they are resecting the oncologic lesion, and to allow optimal healthy tissue conservation. Fluorescent-guided lymph node mapping and subsequent lymphadenectomy have not only been done during distal rectal cancer procedures but also during robotic right hemicolectomy with complete mesocolic excision (CME) for rightsided colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that not only does Firefly allow for the detection of vasculature and confirmation of anastomotic perfusion, but also precise lymph node dissection can be done along the IMA vasculature 22 . Additionally, the Firefly system may be utilized in robotic low anterior resection of rectal neoplasms by injecting ICG dye preoperatively to identify these lesions during surgery 23 . This is referred to as “tattooing” and allows the surgeon to confirm they are resecting the oncologic lesion, and to allow optimal healthy tissue conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative visualization of the ureter using ureteral stent or indocyanine green has been reported as an effective way to prevent ureteral injury. Intraoperative visualization of the ureter with fluorescence using indocyanine green may be the best way to prevent ureteral injury [ 9 ]. Cases 1, 2, 4, 5, and 6 in our study could have been avoided if this method had been used.…”
Section: Discussionmentioning
confidence: 99%
“…En las últimas dos décadas ha habido un papel y un impacto crecientes de los procedimientos mínimamente invasivos para las enfermedades del colon y el recto (4). Para el cáncer colorrectal en particular, los resultados a largo plazo han mejorado como resultado de los avances en la técnica quirúrgica y las terapias multimodales perioperatorias (5).…”
Section: Introductionunclassified
“…Para el cáncer colorrectal en particular, los resultados a largo plazo han mejorado como resultado de los avances en la técnica quirúrgica y las terapias multimodales perioperatorias (5). Los avances tecnológicos novedosos y las habilidades quirúrgicas mejoradas han permitido a los cirujanos realizar anastomosis colorrectales bajas y ultrabajas en lugar de una colostomía permanente (4).…”
Section: Introductionunclassified